Features on the dorsal surface of the sacrum - Sayee Rajangam; Safeer Khan; Flossie Jayakaran (Wolters Kluwer Medknow Publications, 2014)
Background and Aims: The present study was undertaken to report the observed variations in the features on the dorsal surface of the sacrum. Materials and Methods: Twelve female and 10 male sacra were used for the study. The studied features on the dorsum of the sacrum include sacral hiatus, spinous and articular tubercles (AT) of the median and intermediate sacral crests and sacral foramina. Results: The apex of the sacral hiatus was an inverted V in 10 and a U in 12 (54.5%) sacra. The apex was located between S3 and S4 in 12 (54.6%) and the base at S4 in 21 (95.5%) sacra. Spinal tubercles (ST) and AT were absent in two each of the sacra. Sacral foramina were seen five in one male sacrum along with ossified sacrococcygeal joint. In two female and two male sacra, sacralization of the 5 th lumbar vertebra were noted. Six features were a common occurrence in more than 50% of the female and male sacra: U-shaped apex; apex location between S3 and S4; base location below S4; medium length of hiatus with apex between S3 and S4; three numbers of ST; and four numbers of sacral foramina. Three features were commonly seen for the female sacra: U apex between S3 and S4; base below S4; and four numbers of AT. For the male sacra, the four common features were: V-shaped apex; base below S4; three AT; and circular sacral foramina. Conclusion: The implications from the findings of the present study are directed toward the importance of the variations in the features of the dorsal surface of the female and male sacra for any procedures involving caudal epidural anesthesia.